1989
DOI: 10.1002/eji.1830191011
|View full text |Cite
|
Sign up to set email alerts
|

The restrictive role of sialic acid in antigen presentation to a subset of human peripheral cd4+ t lymphocytes that requires antigen‐presenting dendritic cells

Abstract: Dendritic cells from human epidermis, i.e., Langerhans cells (LC), are more potent antigen-presenting cells (APC) than APC from peripheral blood in proliferative in vitro responses of helper T lymphocytes to various soluble antigens. Analysis of antigen recognition by CD4+ T lymphocyte clones indicated that this increased potency of LC as APC results from a preferential requirement for LC of part of the T cell population. These T cells show a long-lasting restoration of antigen responsiveness to peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…PBMC were isolated by density centrifugation on Lymphoprep (Nycomed, Torshov, Norway), treated with neuraminidase (Koch-Light, Suffolk, GB) to remove sialic acid [24] and cultured for 10 days in the presence of Dp proteins (CSL), the last 5 days in the presence of 50 U/ml rIL 2 (rIL 2; Cetus, Emeryville, CA). On day 10 cloning was performed, in 96-well flat-bottom culture plates, by LD at 0.3 cells/well and nonspecific stimulation with 1 p,g/ml PHA (Difco, Detroit, MI) in the presence of 3000 radirradiated PBMC ( 106/ml) from two different unrelated donors, 3000 rad-irradiated cells (l@/ml) of an EBVtransformed B cell line (JY) and rIL2 (50 U/ml).…”
Section: Cloning Procedures Of Dp-specific T Cellsmentioning
confidence: 99%
“…PBMC were isolated by density centrifugation on Lymphoprep (Nycomed, Torshov, Norway), treated with neuraminidase (Koch-Light, Suffolk, GB) to remove sialic acid [24] and cultured for 10 days in the presence of Dp proteins (CSL), the last 5 days in the presence of 50 U/ml rIL 2 (rIL 2; Cetus, Emeryville, CA). On day 10 cloning was performed, in 96-well flat-bottom culture plates, by LD at 0.3 cells/well and nonspecific stimulation with 1 p,g/ml PHA (Difco, Detroit, MI) in the presence of 3000 radirradiated PBMC ( 106/ml) from two different unrelated donors, 3000 rad-irradiated cells (l@/ml) of an EBVtransformed B cell line (JY) and rIL2 (50 U/ml).…”
Section: Cloning Procedures Of Dp-specific T Cellsmentioning
confidence: 99%
“…However, there is some evidence for proadhesive properties of CD43 via receptor ligation [14]. Therefore, there is a suggestion that downregulation of membrane CD43 can weaken repulsion, leading to more efficient contacts via adhesion molecules [15].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion property is due to ligand-receptor interaction that causes cell aggregation or stabilizes cell interaction for other adhesion molecules to mediate cell aggregation. In addition, CD43 binding to its receptor can induce signals through its cytoplasmic domain, promoting cell aggregation [8][9][10][11][12][13][14][15]. CD43 contains three protein-kinase-C phosphorylation sites on the cytoplasmic domain, and further studies have shown its role in cytoplasmic signaling and activation of monocytes, T and B lymphocytes and natural killer (NK) cells [10][11][12][16][17][18][19] through pathways other than those that promote aggregation [19][20][21][22][23].…”
mentioning
confidence: 99%
“…In most experimental settings, lower densities of sialic acid on the surface of DC lead to a more robust T-cell response. Whereas some authors attribute this effect to the improved interaction of adhesion molecules, others prioritize signaling events or higher avidity of T-cell receptors to MHC molecules as the responsible mechanism [74,75].…”
Section: Glycosylation Of Dendritic Cellsmentioning
confidence: 99%